THE RELATIONSHIP BETWEEN EATING AND THE INCIDENCE OF OVERWEIGHT IN TEENAGER CLASS OF XII HOSPITALITY OF SMKN X BATAM - Parisma, Wan Intan (Jurnal Kesehatan Ibnu Sina (j-kis), 2023)
Increased prosperity in the community followed by an increase in education can change lifestyle and diet, from traditional diets to practical and ready-to-eat foods that can lead to unbalanced nutritional quality. The design of this study is a correlational study with a cross sectional approach. The population were all teenagers of class XII Hospitality in SMK X Batam. The sampling technique used Total sampling, namely 53 female students. Independent variables of diet in teenager and the dependent variable is the incidence of overweight. The research instrument used was a dietary questionnaire and an overweight body weight observation sheet. Statistical test used chi square analysis. The results of the chi square test obtained p value = 0.002 <0.05, so Ha was accepted, meaning that there was a relationship between eating patterns and the incidence of excess weight at the age of teenager in class XII SMK X Batam